Impacts of chemical reactions on inclined isothermal vertical plate - Sundar Raj, M.; Nagarajan, Gnanavel; Murugan, V.P.; Muthucumaraswamy, Rajamanickam (Zielona Góra: Uniwersytet Zielonogórski)
An accurate parameterization of an irregular surge across a continuously propelled circulation through an endless isothermal inclined plate has been investigated in the presence of a first-degree uniform chemical reaction. Both the plate`s temperature and the proximal intensity are increased systematically. To evaluate non-dimensional equations, the Laplace transform is utilized. The effect of velocity components on a range of physical parameters is investigated which include Sc, Pr, Gr, Gc, ?, K and t. A proportionate increase of velocity with Gr and Gc was prominent.
Keywords: expedited; inclined slab; heat transmission; mass transfer; chemical reaction